PENGARUH REGANGAN PADA MATERIAL LOGAM BAJA TERHADAP KEKERASAN DAN SIFAT GETARAN - helanianto helan (INOVTEK POLBENG, 2019)
History shows the development of human thinking patterns that are more advanced in understanding, utilizing and further knowing the causes and results of the findings obtained. Humans find strong material, with complex phenomena and unknown compilation yet, but they have felt of great benefit. And with the development of knowledge, conventional and modern processes are carried out to achieve the goal. Namely with the methods carried out, managing the metal has a different impact than before, then the metals change physically and non-physically. This study aims to learn more about the relationship of metals treatment to hardness and the vibration that occurs in metal material that is disputed. This research uses experimental methods on materials with treatment and un-treatment to study the correlation, which is supported by the method of testing the hardness test and vibration test. The results show that increased strain on hardness and vibration patterns of metal have full or correlated. In this study, un-load raw materials was obtained an average hardness value of 52.28 HRB with an average vibration of 1.448 mm / s. While the specimen with tensile load obtained an average hardness of 52.34 HRB with an average vibration pattern of 1.7388 mm / s. These results show an increase in hardness of 0.115% and vibration of 20.028%, which is an increase in stretching effect. It can be concluded, however that increasing strain loads increase the hardness and vibration of low carbon steel equivalent ST-37.